Three-dimensionally printed porous biomimetic composite for sustained release of recombinant human bone morphogenetic protein 9 to promote osteointegration. (October 2021) - Zhu, Zhengqing; Li, Xin; Li, Youbin; Zhu, Liwei; Zhu, Chenyi; Che, Zhenjia; Huang, Lanfeng
Graphical abstract: Highlights: A composite scaffold has been developed to control the release of recombinant human bone morphogenetic protein 9. The composite scaffold was composed of 3D-printed Ti6Al4V and thermosensitive collagen. The composite scaffold could induce osteogenic differentiation and promote the expression of osteogenic markers in vitro. The osseointegration between bone and scaffold was improved in bone defect. Abstract: Three-dimensionally printed porous titanium alloys prepared using the electron beam melting (EBM) technology have customized structures and a low elastic modulus. They can promote the repair of bone defects. Growth factors can enhance the biological activity of plants in vivo, and bone morphogenetic protein 9 (BMP9) is the key factor for osteogenesis. The purpose of this study was to evaluate a porous titanium implant prepared using the EBM technology with temperature-sensitive collagen mixed with recombinant human (rh) BMP9 as a composite scaffold to be continuously provided to enhance osteogenesis in rabbit femoral defects. The in vitro experiments verified cell proliferation, proliferation and application of the composite stent, the degree of release of temperature-sensitive collagen to rhBMP9, and the osteogenesis-inducing effect of the composite stent on bone marrow mesenchymal stem cells. In vivo, the rabbit femoral defect model was used to evaluate the effects of the composite on osteointegration and bone ingrowth. The results showed that the composite scaffold had good biocompatibility and provided bioactive growth factors for bone repair. Further, the release of rhBMP9 significantly enhanced osteogenesis in and around the porous scaffolds. This method helps to study bioactive coating on the titanium alloy surface of patients with bone defects.